2021
DOI: 10.1055/a-1274-0773
|View full text |Cite
|
Sign up to set email alerts
|

Application Possibilities of a New Preloaded Nasolacrimal Duct Intubation System

Abstract: Introduction The LacriJet (FCI S. A. S. – France Chirurgie Instrumentation, Paris, France) represents a novel, simplified and preloaded system for monocanalicular or monocanaliculonasal nasolacrimal duct intubation. It is a further development of the Masterka and shall reduce the intubation time during the surgical procedure. The aim of the present study was to present first experiences with this system for different indications. Material and Methods All patients who underwent nasolacrimal duct intub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…6,7,13,18 In the retrospective case series of Mihailovic et al 3 out of 12 patients post lacrijet intubation experienced an early tube dislocation or a complete loss of the tube. 14 Fayet et al also described several difficulties when using the Lacrijet system that occurred more in his preliminrary study. The techqniue has been gradually modified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7,13,18 In the retrospective case series of Mihailovic et al 3 out of 12 patients post lacrijet intubation experienced an early tube dislocation or a complete loss of the tube. 14 Fayet et al also described several difficulties when using the Lacrijet system that occurred more in his preliminrary study. The techqniue has been gradually modified.…”
Section: Discussionmentioning
confidence: 99%
“…Mihailovic et al presented a retrospective study of children and adults who were intubated with Lacrijet tube. 14 It is a smaller cohort study of 12 patients with CNLDO, canalicular laceration and eyelid reconstruction. They concluded that Lacrijet can be used in the above mentioned indications, but they did not discuss the success rate and nor did they measure the operative time.…”
Section: Discussionmentioning
confidence: 99%